Investigation of ski movements in carving turn: a pilot study - Nakazato, K.; Yuasa, K. (4th International Congress on Science and Skiing, 2007)
INTRODUCTION: With the appearance of the carving ski, alpine and recreation ski turn techniques have changed dramatically. over the past several years. National Ski Method of Japan shows that two important factors caused by carving turn are on-edge angle and skier's loading. The purpose of this study was to suggest effective parameters for comparison of ski movements between experienced and intermediate skiers.